DIGITAL COMMUNICATION ETHICS OF CONTENT CREATORS IN TERNATE CITY (Cristian Fuchs' Approach and Jurgen Habermas's Communicative Action) - Wahyuni Bailussy; Tuti Bahfiarti; Mulyadi Mau (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study analyzes Christian Fuchs' approach to community ethics in the context of the development of digital space in the city of Ternate. In the midst of a pluralistic society firmly rooted in communal values, this approach offers an ethical foundation for building a digital space that is not only technical, but also socially and ethically meaningful as well as ethically and ethically communicated. Case studies such as content creators who fill social media in the city of Ternate. Social media users showed how communication practices in the digital space in the community need to be balanced with ethics that uphold the value of local wisdom in Ternate City so that there is no division and can strengthen solidarity and collective responsibility in the use of digital technology. This analysis also connects Christian Fuchs' thoughts and approaches that emphasize the importance of ethical, fair and participatory communication on social media. Thus, this study emphasizes that the development of an ethical, equitable and participatory digital space requires the integration of digital communication ethics, social participation, and criticism of the global digital dominance structure, which has an impact on the quality of content that deviates from ethics as an ancestral wealth called local wisdom.